Electrical impedance myography for reducing sample size in Duchenne muscular dystrophy trials. Issue 1 (25th December 2019) - Leitner, Melanie L.; Kapur, Kush; Darras, Basil T.; Yang, Michele; Wong, Brenda; Dalle Pazze, Laura; Florence, Julaine; Buck, Martin; Freedman, Laura; Bohorquez, Jose; Rutkove, Seward; Zaidman, Craig
Abstract: Objective: To evaluate the sensitivity of electrical impedance myography (EIM) to disease progression in both ambulatory and non‐ambulatory boys with DMD. Methods and Participants: A non‐blinded, longitudinal cohort study of 29 ambulatory and 15 non‐ambulatory boys with DMD and age‐similar healthy boys. Subjects were followed for up to 1 year and assessed using the Myolex ® mView TM EIM system as part of a multicenter study. Results: In the ambulatory group, EIM 100 kHz resistance values showed significant change compared to the healthy boys. For example, in lower extremity muscles, the average change in EIM 100 kHz resistance values over 12 months led to an estimated effect size of 1.58. Based on these results, 26 DMD patients/arm would be needed for a 12‐month clinical trial assuming a 50% treatment effect. In non‐ambulatory boys, EIM changes were greater in upper limb muscles. For example, biceps at 100kHz resistance gave an estimated effect size of 1.92 at 12 months. Based on these results, 18 non‐ambulatory DMD patients/arm would be needed for a 12‐month clinical trial assuming a 50% treatment effect. Longitudinal changes in the 100 kHz resistance values for the ambulatory boys correlated with the longitudinal changes in the timed supine‐to‐stand test. EIM was well‐tolerated throughout the study. Interpretation: This study supports that EIM 100 kHz resistance is sensitive to DMD progression in both ambulatory and non‐ambulatory boys. Given the technology's ease of use and broad age range of utility it should be employed as an exploratory endpoint in future clinical therapeutic trials in DMD. Trial Registration: Clincialtrials.gov registration #NCT02340923